The Economic Implications of an Incidental Durotomy. Issue 19 (1st October 2016) - Schroeder, Gregory D.; Kepler, Christopher K.; Alijanipour, Pouya; Kurd, Mark F.; Hollern, Douglas; Kumar, Priyanka; Radcliff, Kris E.; Rihn, Jeffery A.; Anderson, D. Greg; Hilibrand, Alan S.; Vaccaro, Alexander R.
Abstract : Study Design: Case–control. Objective: The aim of this study was to determine the economic impact of an incidental durotomy in spine surgery. Summary of Background Data: An incidental durotomy during spine surgery does not affect long-term outcomes, but as reimbursement moves toward bundled payments, it may substantially affect the profitability of spine surgery. Methods: A retrospective review of a prospectively collected morbidity and mortality database identified all patients with an incidental durotomy between January 1, 2012, and January 11, 2013. Subjects with a dural tear were matched to controls (1 : 2) without a dural tear, and the total charges for one year were collected. Controls were required to meet the following criteria: Age ±5 years; Charlson Comorbidity Index (CCI) ±1; Date of surgery ±2 years; Exact region of the spine, but not the exact level ( i.e., lumbar → lumbar); Exact type of fusion ( i.e., approach, instrumentation); Exact number of levels fused; Use of rhBMP-2; Number of levels decompressed ±1. Results: Two controls without a dural tear could be identified for 57 patients who sustained an incidental durotomy. No difference in demographic data, emergency room visits, hospital readmissions, or revision surgeries between the groups was identified. Patients with an incidental durotomy had a longer operative time by 30.6 ± 8.5 minutes ( P  < 0.01), longer length of stay by 0.89 ± 0.27 days ( P  = 0.0001), and an increase in their average initial hospital charge by 18%. No increase in surgeon-based charges or hospital-based charges after the initial visit was identified. Conclusion: An incidental durotomy significantly increases the initial hospital charges for patients undergoing spine surgery; however, in this study it has no effect on surgeon-based charges or on hospital-based charges after discharge. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text